Moderation Effect of Physical Activity on the Relationship Between Fear of COVID-19 and General Distress: A Pilot Case Study in Arabic Countries - Alsalhe, Tareq A.; Aljaloud, Sulaiman O.; Chalghaf, Nasr; Guelmami, Noomen; Alhazza, Dallal W.; Azaiez, Fairouz; Bragazzi, Nicola Luigi (Frontiers in Psychology, 2020)
Aims: the effects of fear of Covis-19, physical activity and gender on negative stress (Distress) in an Arab population by the method of structural equations based on partial least squares. Material and methods: The 459 participants from four Arab countries (age M = 33.02, SD age = 8.46 are divided by sex into women (n = 237) and men (n = 222). The level of education was basic (<9 years of study; n = 144), secondary / vocational (between 9 and 12; n = 178) and university (n = 137). The COVID-19 Fear, International Physical Activity questionnaire (IPAQ) and Perceived Stress (PSS10) questionnaires were disseminated on emails and on social networks via Google Forms. SMARTPLS software version 3.2.9 was used to model the relationships between the variables. Results: The results confirmed the links between gender, physical activity, fear of Covid-19 and gender. They showed that a significant mediating effect of Covid-19 Fear in the relationship between gender and General Distress. Also, physical activity influenced fear of Covid-19, but it depends on gender. In addition, the model highlighted the presence of an effect moderation of physical activity. Conclusion: From the model presented in this study, it is clear that the COVID-19 pandemic has an impact on psychological distress in the target populations. The impact of physical activity on psychological distress is shown to be very important during the pandemic phase.